Can process portfolios affect students' writing self-efficacy? - Iolie Nicolaidou (My University, 2012)
Can process portfolios that support students in goal setting, reflection, self-evaluation and feedback have a positive impact on students' writing self-efficacy? This article presents the findings of a yearlong study conducted in three 4th grade elementary classes in Cyprus where paper-based and web-based portfolios were implemented to help students document their progress. Using a non-equivalent pre-test post-test design it was found that the self-efficacy of students who used portfolios for their essay writing process over an academic year increased significantly (p< .05), compared to control students who did not. The increase of writing self-efficacy corresponded to an increase of writing performance (p< .05). This study also verified the connection between Bandura's self-efficacy theory and portfolio affordances. Instructional implications for portfolio implementation are offered.
Keywords: Self-efficacy; Students; Cyprus